The first report of the ante-mortem diagnosis of Ollulanus tricuspis infection in two dogs - KATO, Daiki; OISHI, Mariko; OHNO, Koichi; NAKASHIMA, Ko; WADA, Atsuhito; MORITA, Tatsushi; IMAI, Soichi; TSUBOI, Masaya; CHAMBERS, James K.; UCHIDA, Kazuyuki; TSUJIMOTO, Hajime (Journal of Veterinary Medical Science, 2015)
Ollulanus tricuspis is a small nematode parasite of the stomach, and its infection has been reported worldwide in cats but only one report in dogs as post-mortem diagnosis. Two dogs, kept in the Tokyo area, were presented for chronic vomiting. Chronic gastritis was diagnosed histologically, and many nematodes were detected in endoscopically-biopsied gastric samples and in the mucus of vomitus in both dogs. The parasites were small (<1 mm), and their morphological characteristics were consistent with those previously reported for O. tricuspis. The symptoms in one dog completely disappeared after anthelmintic therapy. To our knowledge, this is the first report describing ante-mortem diagnosis of spontaneous gastric O. tricuspis infection in dogs in which infectivity and pathogenicity of the nematode are suggested.